The Impact of a Family-Centered Problem-Solving Program on Emotional Regulation of Mothers of Students with Autism Spectrum Disorder - K. Kakabaraee, Ph.D.; G. A. Afrooz, Ph.D.; M. Seidi, Ph.D. (خانواده و پژوهش, 2023)
This study set out to determine the impact of a family-centered problem-solving program on emotional regulation of mothers of students with autism spectrum disorder. The research had a pretest-posttest control group design with a follow-up session. The statistical population of the study was comprised of all mothers of students with autism spectrum disorder in Kermanshah in 2018-19 school year. Sixty-four students with autism spectrum disorder were studying in Besharat School which serves autistic students. Thirty mothers of the aforementioned students were selected using purposive sampling method and were randomly assigned to experimental (N=15) and control (N=15) groups. The experimental group was subjected to the family-centered problem-solving training for ten sessions, while the control group did not receive any intervention. The research instrument included the Emotion Regulation Questionnaire (Gross & John, 2003). The obtained data were analyzed via repeated measures analysis. The results indicated that the family-centered problem-solving program had a significant effect on the emotional regulation of the subjects and this effect was stable over time in the follow-up stage (p<0.01). The family-centered problem-solving program can improve the emotion regulation of mothers of children with autism spectrum disorder. Hence, it is of high importance to utilize this program for mothers with autistic children.